2018
DOI: 10.4236/oalib.1105038
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Practices of Teachers in Selected Primary and Secondary Schools in Jamaica

Abstract: The purpose of the study was to determine if there were differences in the perceptions of primary and secondary school teachers' classroom assessment practices in region one in Jamaica. Seven research questions guided the study. An analytic survey research design was used to answer the research questions. A stratified random sampling method was used to select 225 teachers. However, a total of 157 (64 primary & 93 secondary) school teachers participated in the study. Data were collected through the use of a web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Similarly, Onyefulu (2018) discovered that teachers often used traditional assessment methods such as short answers, multiple-choice, fill-in-the-blanks, and closed-book tests. Again, the findings of this study concur with Suah and Ong (2012) that Malaysian in-service teachers often use traditional assessment methods.…”
Section: Discussion Of Methods and Tools Employed In Assessing Learnersmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Onyefulu (2018) discovered that teachers often used traditional assessment methods such as short answers, multiple-choice, fill-in-the-blanks, and closed-book tests. Again, the findings of this study concur with Suah and Ong (2012) that Malaysian in-service teachers often use traditional assessment methods.…”
Section: Discussion Of Methods and Tools Employed In Assessing Learnersmentioning
confidence: 99%
“…Results from the study revealed that teachers mostly follow traditional assessment practice such as; oral presentations, objective type test, question answering, and homework during the instruction, and disregarding alternative assessment practices such as -group projects, one-minute test, presentation, portfolio, self and, peer assessment practices. Onyefulu (2018) conducted a study in Jamaica to determine the classroom assessment of primary (n=64) and secondary (93) school teachers. The results revealed that the teachers often used restricted essays, multiple-choice, fill-in-the-blanks, short answers, closed-book tests, and portfolios.…”
Section: Teacher Assessment Practicesmentioning
confidence: 99%
“…Other researchers also found that elementary teachers used more varied assessment methods, including informal evidence and observations, while secondary teachers used paper-pencil objective tests, whether commercially prepared, teacher-made, or derived from textbooks (Brookhart, 2009(Brookhart, , 2013Guskey & Link, 2019;Ong, n.d.;Vlachou, 2018;Zhang & Burry-Stock, 2003). I found only one study investigating teachers' assessment practices in the Jamaican context: Onyefulu (2018). Onyefulu (2018) surveyed 157 primary and secondary school teachers in Region 1 in Jamaica and confirmed testing dominance with 51% of the primary school teachers and 85% of the secondary school teachers surveyed reporting that they most frequently used closed-book tests to assess their students.…”
Section: Assessment Tools and Strategies Used By Teachersmentioning
confidence: 99%
“…Additionally, there is a dearth of empirical research on assessment in Jamaica, in general, and the formative use of assessment in the Jamaican context (Williams-McBean, 2021). I found only one paper on the assessment strategies Jamaican teachers used, and it focused on only one of the seven education regions in Jamaica (Onyefulu, 2018). Additionally, Onyefulu (2018) reported that she could find no published article on Jamaican teachers' classroom assessment practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation